IMPLEMENTASI METODE MULTIPLICATIVE CONGRUENTIAL RANDOM NUMBER GENERATOR (MCRNG) UNTUK PELAKSANAAN UJIAN PADA SMPN 13 KOTA BENGKULU - yessi mardiana; Devina Ninosari (JUTIM (Jurnal Teknik Informatika Musirawas), 2026)
The implementation of examinations is one of the important activities in the learning evaluation process to measure the level of understanding and the achievement of students' competencies. In practice, problems are often encountered in the form of possible cheating due to similarities in the sequence of questions received by exam participants. Therefore, a method is needed that can effectively produce question randomization to improve the fairness and objectivity of the examination process. This study aims to implement the Multiplicative Congruential Random Number Generator (MCRNG) method in the examination system at SMPN 13 Kota Bengkulu as a mechanism for automatically randomizing the sequence of questions. The MCRNG method is used to generate pseudo-random numbers, which are then utilized in the process of randomizing exam questions. The study was conducted through the stages of system requirements analysis, randomization algorithm design, implementation of the MCRNG method in the examination system, and testing the results of the randomization that produced. Testing was conducted to determine the method's ability to generate variations in the sequence of questions that are different for each exam participant. The research results show that the MCRNG method is able to produce question randomization quickly and effectively with a good level of question sequence variation. The implementation of this method can reduce the likelihood of participants receiving the same arrangement of questions, thereby helping to minimize the potential for cheating during the exam. In addition, the system that was built is able to support a more structured, efficient, and transparent exam process. Thus, the application of the Congruential Random Number Generator (CRNG) method in the implementation of exams at SMPN 13 Kota Bengkulu can be an effective solution in improving the security, fairness, and quality of computer-based learning evaluation processes.